PENGARUH EMPLOYEE RELATION TERHADAP KEPUASAN KOMUNIKASI KARYAWAN PDAM TIRTANADI CABANG SEI AGUL - Sigit Hardiyanto (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
One form of a public relations governing relations between companies and their employees are employee relations. Employee relations done between other to create form a connection or communication two directions the management of with the karyawannyadalam efforts to build cooperation and harmonious relations between. PDAM Tirtanadi the giants agul is a company that routinely activity employee relations. This study attempts to know whether there are relations between variables employee relations with a variable satisfaction komunikasi.jenis research is correlational research with the quantitative approach. As for population in research is all the employees PDAM Tirtanadi the branch sei agul which consisted of 60 of the calculation on, obtained value rxy 0,5975, while r table namely 0,254 with the number of respondents 60 and the economic situation of significance 5 percent. Its requirements is if r count & gt; of r table so ha received and h0 rejected, and if r count & lt; r table so h0 received and ha rejected.The calculation on is r count & gt; of r table. Thus, h0 were rejected and ha accepted, which means activities employe relations very influential significant impact on satisfaction employees communication.Keywords: Public Relations, employee relations, Communication Organization